Recommendation for Physical Activity for Patients Suffering from Osteoporosis - Agata Horbacz; Halina Romualda Zięba; Alena Buková; Kateryna Tovt (Lesya Ukrainka Volyn National University, 2020)
Introduction. Osteoporosis is currently the most common bone disease affecting a significant part of the population. The occurrence of this disease increases with the increasing average life expectancy. One should not forget that prevention is the key component to avoid osteoporosis and one of the most important parts of the prevention are lifestyle, eating habits, adequate intake of minerals and appropriate physical activity. Along with the pharmacologic treatment, appropriate physical activity is proved to significantly mitigate the negative effects of the disease. The aim of this study is to expand the knowledge about patients´ awareness of osteoporosis and provide recommendations for physical activity for patients with osteoporosis. Methods. We approached patients suffering from osteoporosis (n=96), 78 female patients, and 18 male patients. The average age of the participants was ±65. Our research was conducted at specialized outpatient clinics in eastern Slovakia. For data collection, we used a non-standardized questionnaire that was part of the questionnaire battery explicitly designed for this research. We focused on the basic information about the health conditions including patients´ awareness of the appropriate physical activity with regard to their diseases. Based on these findings we suggested a set of recommendations for the performance of physical activity for patients suffering from osteoporosis. Results. Our findings show that 73 % of patients were informed about their health condition and most patients receive this information from their primary care physicians. 45 % of the respondents received information about the appropriate physical activity in treating osteoporosis from their primary care physicians and 22 % from the nursing staff. 21 % of respondents were not interested in any information regarding physical activity. 57 % of the patients in our sample spend leisure time gardening and 76 % of respondents spend leisure time doing household chores. Further leisure time activities included shopping (45 %) and reading (36 %). Watching TV and computer-related activities were identified by 34 % of respondents and 10 % of respondents performed recreational physical activity, especially hiking and walks. Conclusion. Most respondents received information about their diagnosis and physical activity from their physicians, nursing staff, or media. It is encouraging that patients were aware of the appropriate physical activity and they also try to learn about it through various information channels, however, only a small number of patients in our sample perform specific physical activity in their leisure time.